1993
DOI: 10.1021/j100123a041
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence as a probe of the adsorption of gaseous boranes onto the surface of cadmium selenide crystals

Abstract: Gas-phase adsorption of several boranes (BF3, MeBBr2, MelBBr, and Et3B) onto the surface of etched, singlecrystal n-CdSe quenches the band gap photoluminescence (PL) relative to its intensity in vacuum (pressure -Torr). The PL quenching is consistent with the Lewis acidic nature of the boranes and is dependent on substituents: PL quenching follows the order BF3 > MeBBr2 > MezBBr > Et3B. The magnitude of the PL quenching can be fit to a dead-layer model, permitting an estimate of the adduct-induced expansion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Third, because the electronic properties are controlled by a very thin (and ideally monomolecular) layer, such a layer may potentially be used for fine-tuning interface electronic properties without impeding carrier transport through the interface. Indeed, various types of such molecular treatment-induced changes in V s and/or SRV have been reported for GaAs, ,, Si, ,, CdS, , and CdSe. − ,, …”
Section: Introductionmentioning
confidence: 99%
“…Third, because the electronic properties are controlled by a very thin (and ideally monomolecular) layer, such a layer may potentially be used for fine-tuning interface electronic properties without impeding carrier transport through the interface. Indeed, various types of such molecular treatment-induced changes in V s and/or SRV have been reported for GaAs, ,, Si, ,, CdS, , and CdSe. − ,, …”
Section: Introductionmentioning
confidence: 99%
“…The surface properties of metals and semiconductors dictate many of the electronic characteristics of optoelectronic devices such as photovoltaic cells, photocathodes, detectors, and Schottky diodes. − Therefore, development of methods to control surface properties, particularly through chemical treatments, is an area of great interest. − Recently, we and others have begun to explore the potential of organic compounds for surface modification. − In ultrahigh vacuum a few ligands have been reported to induce work function changes of >1 eV. , Similarly, Evans and co-workers showed that alkanethiols and perfluorinated alkanethiols on gold yielded surface potential changes with magnitudes greater than 1.0 V. , …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Recently, we and others have begun to explore the potential of organic compounds for surface modification. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] In ultrahigh vacuum a few ligands have been reported to induce work function changes of >1 eV. 33,34 Similarly, Evans and co-workers showed that alkanethiols and perfluorinated alkanethiols on gold yielded surface potential changes with magnitudes greater than 1.0 V. 35,36 For the purpose of surface modifications, organic binders have a priori the advantages of structural versatility and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…We have interpreted semiconductor PL intensity enhancements as arising from the formation of a surface charge-transfer complex with a Lewis base; , as noted above, adsorption of the base can shift electron density from surface states back into the bulk solid, decreasing the depletion width and enhancing PL intensity. A possible binding scenario might be that the oxygen atom of the epoxide can serve as an electron donor toward coordinatively unsaturated surface Cd sites.…”
Section: Resultsmentioning
confidence: 87%